Biblioterapi untuk Meningkatkan Perkembangan Sosial pada Anak Prasekolah - Eka Adimayanti; Dewi Siyamti; Hapsari Windayanti (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2022)
Abstract Bibliotherapy is psychotherapy support through reading material to help someone who is experiencing personal problems or for other therapeutic purposes. Reading books are one of the media that teachers can use to stimulate children's social skills. Community Service Activities with the title